PENERAPAN KEGIATAN MGMP GUNA MENINGKATKAN KEMAMPUAN PENGGUNAAN MEDIA PEMBELAJARAN DAN LINGKUNGAN SEKOLAH SEBAGAI SUMBER PROSES PEMBELAJARAN - Nelson Tambunan (Smart Education, 2020)
Abstract: This research is a school action research, with the research subjects of 16 teachers of SMA Negeri 2 Lintongnihuta. The object in this study is the result of the assessment of the ability of teachers in the use of learning media and the school environment as a source of learning in the teaching and learning process through the eye teacher deliberation activity. The instrument used was the Observation Sheet. Based on the results of the assessment, the number of teachers in cycle I who have been able to use learning media and the school environment as a learning resource in the